2022
DOI: 10.29210/1202221160
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi evaluasi model kirkpatrick terhadap kualitas sistem pembelajaran

Abstract: Penelitian ini bertujuan untuk mengetahui dan menganalisis persepsi mahasiswa UPBJJ-UT Ternate atas kualitas pembelajaran di Universitas Terbuka dengan evaluasi Kirkpatrick, dan pendekatan deskriptif kuantitatif dengan tujuan untuk mendiskripsikan objek penelitian ataupun hasil penelitian. Populasi dalam penelitian ini adalah Mahasiswa UPBJJ-UT. Teknik sampling yang digunakan adalah non probability sampling, dengan menggunakan metode proporsional random sampling. Dengan Jumlah sampel dalam penelitian ini adala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Assessment at this stage will also explain the differences between what they have learned before and after this program (Karim et al, 2022). The fourth stage: the level of performance/result, aims to measure the extent to which the curriculum has helped achieve the previously set goals and what has been achieved as the final result after the learning process (Effendi et al, 2022).…”
Section: Kirkpatrick Model Program Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment at this stage will also explain the differences between what they have learned before and after this program (Karim et al, 2022). The fourth stage: the level of performance/result, aims to measure the extent to which the curriculum has helped achieve the previously set goals and what has been achieved as the final result after the learning process (Effendi et al, 2022).…”
Section: Kirkpatrick Model Program Evaluationmentioning
confidence: 99%
“…Several recent studies such as those conducted by Effendi et al (2022) regarding the implementation of the evaluation model Kirkpatrick concluded that at the reaction level, students showed a level of satisfaction with the suitability of the material with the module. At the learning level, students are satisfied with the relevance of the material in everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluasi tahapan reaksi merupakan sebuah proses evaluasi terhadap respon terkait perasaan, pemikiran, maupun pendampingan, serta pelaksanaan lingkungan belajar (Effendi et al, 2022). Pembelajaran tersebut bisa disebutkan sebagai suatu proses hubungan peserta didik, baik itu dengan pendidik maupun sumber belajar yang ada pada lingkungan belajar.…”
Section: Evaluasi Model Kirkpatrick Reaksiunclassified
“…Mengukur proses pembelajaran yaitu transfer pembelajaran. Pembelajaran berkesinambungan terhadap sejauh mana para peserta dapat mengubah sikap, menambah pengetahuan, maupun meningkatkan keterampilan (Effendi et al, 2022).…”
Section: Evaluasi Model Kirkpatrick Tahapan Pembelajaranunclassified
See 1 more Smart Citation